Tabi-tabi sa pagsasantabi : kritikal na tala ng mga lesbiana at bakla sa sining, kultura, at wika - Evasco, Eugene Y.; Evasco, Eugene Y.; Pineda, Roselle V.; Rodriguez, Rommel B. (Quezon City : University of the Philippines Press, 2003)
Aspects of arts, culture, and language of gay and lesbian in the Philippines; collection of articles.
Includes bibliographical references.
In Tagalog.
Keywords: Homosexuality -- History -- Miscellanea; Lesbians -- History; Gays men -- History